Cone Penetration Testing 2022 : proceedings of the 5th International Symposium on Cone Penetration Testing (CPT'22), 8-10 June 2022, Bologna, Italy /: proceedings of the 5th International Symposium on Cone Penetration Testing (CPT'22), 8-10 June 2022, Bologna, Italy. (2022) - Unknown
No abstract available